The History of Wrongful Execution - Smith, Bruce P. (2005)
Since the refinement of forensic DNA analysis in the early 199os, the problem of wrongful execution -the execution of persons who are actually innocent or the risk that such persons might be executed-has received considerable attention from scholars, legal practitioners, politicians, jurists, and social activists. The history of wrongful execution, however, remains unwritten. This Article demonstrates that the problem of wrongful execution, although often considered to be a modern-day concern, preoccupied leading Anglo-American legal commentators in the seventeenth and eighteenth centuries. Troubled by several notorious instances of wrongful execution, prominent writers such as Matthew Hale and William Blackstone urged courts to adopt stricter evidentiary safeguards designed to reduce the risk that innocent persons would be executed. In nineteenth-century America, criminal justice administrators sought to preserve the legitimacy of the death penalty by denying the existence of a wrongful execution problem and by selectively instituting safeguards designed to prevent wrongful executions from occurring. In recent decades, several factors including, most notably, the increased difficulty of identifying irrefutable cases of wrongful execution-have limited the capacity of wrongful execution to serve as a catalyst for legal reform. This Article concludes by suggesting that recent evidentiary proposals designed to reduce the risk of wrongful convictions and wrongful executions are not only desirable, but reflect a return to concerns prevalent at the time of our nation's founding